(3GdJMdjd GdGMUGFj GdGSGSj HGSJNOGe (BSPSSs - (3eMahX CMeO(B, (3LhOIs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2008)
(3eaGgje CSGSjI aj GdEMUGA , GdJYGed eY (Bspss(3,GdJYGed eY GdHjGfGJ , GdGMUGAGJ GdhUajI , ebGQfI GdeJhSWGJ , GdQShe GdHjGfjI ef NdGd (Bgraphs(3, JMdjd GdJHGjf , GdGQJHGW hGdGfMOGQ , KHGJ COGI bjGS s
(3HjHdjhZQGajG U(B.345s
Keywords: (3GdGMUGA(B-(3eYGdLI GdHjGfGJs; (3JMdjd GMUGFjs